Peningkatan Kompetensi Guru dalam Menerapkan Metode Jigsaw melalui Pendampingan - Siwi Saptono Raharjo (Universitas Pancasakti Tegal, 2018)
The aimed of this research was to develop teacher’s competency in implementing jigsaw method. The participants of the research were teachers of third and fourth grade of SD Negeri Purwahamba 01 UPTD Dikbud Suradadi sub-district of Tegal regency. The data collection techniques were comprehension test and learning observation. The training was done through two cycles which each cycle consisted of three meetings. The results indicated the skill of implementing method was raised 16.93 point or 24.51% from 69.05 in cycle I and raised to 85.98 in cycle II. The training of comprehension concept was raised from cycle I to II 19.98 point or 31.54%, and it was 63.35 from cycle I and 83.33 in cycle II from success indicator 75.00. The conclusion of this research is jigsaw method can develop teacher’s skil